An assessment of the factors contributing to the unavailability of drugs at outpatient pharmacy of tertiary care hospital: an observational study [version 2; peer review: 2 approved] - Abhishek Bakare; Aditya Bhargav (F1000Research)
Introduction Throughout history and up until the present, there has been a medicine shortage. In the early 1920s, there was a shortage of insulin, which is when drug scarcity first appeared in the records. Drug shortages are now more prevalent globally than they were back then. The goal of this essay is to pinpoint the key components that make up a definition for medication shortages and to pinpoint the circumstances that should be considered when reporting drug shortages in databases. Understanding the factors that led certain organizations to create their own definition of a medicine shortage was crucial for achieving these goals. The pharmaceutical regulatory environment can be connected to several reasons why there are medication shortages, including parallel trading, quality standards, and business choices to halt or reduce manufacturing. The many rules governing medicine shortages have not yet been the subject of a thorough investigation. This protocol’s objective is to analyze the pertinent legislative and regulatory frameworks in the European pharmaceutical system that affect medication shortages. The objectives of the study will be the non–availability of drugs at an outpatient pharmacy and to analyze the reason of non–availability of drugs. Methods An observational study will be adopted in this study. It includes a collection of data from the patient coming to the outpatient pharmacy of AVBRH Sawangi (Meghe) Wardha. Expected result It can lead to delayed treatment for patients seeking alternative medication. It can also lead to increased healthcare costs if patients seek alternative treatments that are more expensive or require additional medical care. The unavailability of drugs can also lead to frustration and anxiety for patients who need medication to manage their health condition. It can also negatively impact the reputation of the hospital.